Life satisfaction in Germany after reunification: Additional insights on the pattern of convergence - Inna Petrunyk; Christian Pfeifer (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
The authors update previous findings on the total East-West gap in overall life satisfaction and its trend by using data from the German Socio-Economic Panel (SOEP) for the years 1992 to 2013. Additionally, the East-West gap and its trend are separately analyzed for men and women as well as for four birth cohorts. The results indicate that reported life satisfaction is on average significantly lower in East than in West German federal states and that part of the raw East-West gap is due to differences in household income and unemployment status. The conditional East-West gap decreased in the first years after the German reunification and remained quite stable and sizeable since the mid-nineties. The results further indicate that gender differences are small. But the East-West gap is significantly smaller and shows a trend towards convergence for younger birth cohorts.
Keywords: D63; I31; P36; P46; 330; Germany; Happiness; Life satisfaction; Reunification; Trends